Defending Europe - Andrzej Jacuch (Politeja)
A sustained period of relative peace in Europe has nurtured a culture of stability among societies and countries. However, recent events have suggested that the world is teetering on the precipice of conflict. Russia’s actions have blatantly disregarded the norms and principles that have long served as bedrocks of the European security architecture. The war in Ukraine and the expansion of Russian military capabilities, such as integration with Belarus and cooperation with Iran and North Korea, carry the risk of prolonged conflict and potential escalation. How is Europe preparing for these security threats? What does resilience mean in NATO and EU policy, doctrine and practice? In the face of evolving security threats, Europe is employing a comprehensive approach to resilience, encompassing national and societal measures. The aim of this article is to analyse the concept of strengthening resilience to security threats in NATO and the EU with reference to civil preparedness.